Determinants of Acceptance of the COVID-19 Vaccine in Pregnant Women, Indonesia: A Literature Review - Budiati, Endang; Putri, Dian Utama Pratiwi; supriatin, Supriatin; Sari, Marlynda Happy Nurmalita (Postgraduate, University of Mataram, 2023)
Pregnant woman are a vulnerable group for COVID-19. Efforts to control and prevent COVID-19 are being made with the implementation of vaccination, but the fact is that still many pregnant woman refuse to be vaccinated because of many factors, such as fear, feeling insecure about their health and their babies, so there is a doubt about receiving the COVID-19 vaccine. This research aims to find out determinants of acceptance of the COVID-19 vaccine among pregnant women in Indonesia. This study used a literature review (PRISMA) model for guide. Literacy is limited to articles published in January 2021 until September 2023. The extracted data is synthesized with a narrative approach. The article search obtained 17 selected articles. There are 19 determinants that influence the acceptance of the COVID-19 vaccine among pregnant women in Indonesia, including: knowledge, perception, vaccination history, vaccine information, participation, education, anxiety, employment status, behavior, attitude, history of comorbid diseases, family support, role of health workers, social media information, age, community culture, pregnancy status, ANC frequency, and vaccine safety. The underlying factors behind receiving the COVID-19 vaccine in pregnant woman are very complex and context-specific, varying all the time. Socio-demographic variables play a major role in it